Pendampingan Pembuatan Struktur Organisasi dan Perluasan Pengetahuan Pemasaran Digital pada Yayasan PIPAYA Bogor - Abdillah, Fatimah; Pradana, Egi Adithia (Jurnal Abdimas Dedikasi Kesatuan, 2024)
Organization is a crucial component of the management system, with human resource management receiving particular emphasis. Implementing a good management system can help an organization enhance its performance. One component of the management system required to support performance is the preparation of marketing materials and organizational structures. The Pipaya Foundation is a non-profit organization headed by housewives that is committed to managing aid to orphanages. The goal of the support that was provided in building up the Pipaya Foundation's management system is to help the non-profit organization perform better. In order to conduct this study, quantitative descriptive approaches were used. This study's respondents were Pipaya Foundation administrators and members. This study used a questionnaire that contains various questions about the implementation of organizational management and structure, as well as the usage of digital technologies to sell its services. According to the results of data analysis from responders, the mentorship process can help boost understanding about Pipaya's organizational structure and digital marketing. Respondents' average level of knowledge went from high to very high after receiving governance and digital marketing training. Effective and well-structured management of non-profit organizations, like Pipaya, can boost the productivity of human resources and organizations, thereby supporting the Indonesian people's economy. Keywords: Performance; Non-profit organizations; Orphan Assistance Manager; Marketing; Human resources